TOTAL BAKTERI ASAM LAKTAT, VISKOSITAS, DAN SIFAT SENSORIS SOYGURT DENGAN PENAMBAHAN BUBUK KOLANG-KALING - Fitriansyah, Hanif; ., Nurhidajah; Syadi, Yunan Kholifatuddin (Universitas Muhammadiyah Semarang, 2024)
Soyghurt is a product produced from the fermentation process of soybean juice which utilizes the bacteria Streptococcus thermophillus and Lactobacillus bulgaricus, these bacteria have been widely used in making yogurt. Soybean juice as a substitute for yoghurt has high nutritional value. The galactoman contained in palm fruit has the potential to act as a prebiotic. This research aimed to analyze total lactic acid bacteria, viscosity, and sensory properties with the addition of palm fruit powder. This research used (RAL) Completely Randomized Design with 1 factor, namely the addition of palm fruit powder (0%, 0.5%, 1%, 1.5% and 2%). The results of this study showed that increasing the concentration of palm fruit powder had no significant effect on lactic acid bacteria but had a significant difference in viscosity and sensory (colour, texture, taste) except aroma. The best treatment was the addition of 2% palm fruit powder with characteristics of total lactic acid bacteria (1.1 x 10^8 colonies/gram), a viscosity of 412.72 Mpa.s, and sensory value had a score of 3.61 (close to like)